The Performance of Politics: Caribbean Music and the Anthropology of Victor Turner - Manning, Frank E. (Anthropologica, 2022)
This article addresses a central issue in Victor Turner's anthropological thought: the political dimension of rituals as both tools of social control and processes of emancipation. The ever-recurring tensions between repressive social structures and subversion brought about by the emergence of anti-structures must be negotiated through a constant process of social adjustment. On the one hand, social structures are prone to redress deviations. On the other hand, "communitas" tends to dissolve separation, exclusion, and prohibition. Using the concept of social drama, the author analyzes aspects of political life in the Caribbean islands and shows the role played by music in what he calls "the theater state."